Optimalisasi Peran Keluarga dalam Peningkatan Kesadaran Pencegahan dan Deteksi Dini Kanker Serviks : Optimization of Family Role in Improving Awareness of Cervical Cancer Prevention and Early Detection - Atriany Nilam Sari; Siti Nurhidayati; Revi Gama Novika; Rufidah Maulina; Luluk Fajria Maulida; Nurul Jannatul Wahidah (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Cervical cancer is still the cancer that results in the highest female deaths in Indonesia.. The coverage of early detection of cervical cancer in Indonesia is still 8.29%. It was proven that the screening results in Karanganyar showed that as many as 239 mothers with positive iva tests and 15 mothers were suspected of cervical cancer. The purpose of this community service is to provide health education to the community by maximizing family participation in counseling. The target of this activity is 30 couples at the Mojogedang, Karanganyar. The method carried out includes three stages, namely problem identification, implementation, and evaluation. The result of this community service is to increase awareness to carry out early detection of cervical cancer, and reduce stigma regarding cervical cancer. Health counseling or education activities are expected to be carried out in various places by considering the participation of other family members in counseling